The Catholic Church’s perspective of human dignity as the basis of dialogue with the secular world - Alva, Reginald (Stellenbosch Theological Journal, 2017)
The Catholic Church maintains that the Imago Dei is the ground for human dignity. The secular world, too, endorses human dignity as the foundation for human rights without referring to Imago Dei. The Catholic Church and the secular world both agree on the importance of human dignity, even though they differ on their views about the source of human dignity. In this paper, we shall examine if human dignity can be the basis of a fruitful dialogue between the Catholic Church and the secular world in order to make our world a better place to live. The primary resources for our study are the Church documents on human dignity, and the opinions of distinguished thinkers on the need to promote a culture of dialogue between religions and secular world.